Protective effects of colchicine on testicular torsion/detorsion-induced ischemia/reperfusion injury in rats - Gozukara, Kerem Han; Ozcan, Oguzhan; Ozgur, Tümay; Kaya, Yusuf Selim; Tutuk, Okan (Urology Journal, 2020)
Purpose: To evaluate the short-term use of colchicine on preventing ischemia-reperfusion injury after surgery in an experimental animal model. Materials and Methods: A total of 40 rats were divided into five groups (n = 8). Sham (Sh), ischemia-reperfusion (I/R), I/R and colchicine-treated for once per-operatively (I/Rc1), I/R and colchicine-treated for 5 days postoperatively (I/Rc5), and I/R and placebo given for 5 days (I/Rp) groups. Testicular torsion was created by rotating the testicle 720o in clockwise direction and held for 3 hours. In group I/Rc1 30 minutes before detorsion, p.o. 1 mg/kg mL infusion of colchicine was given only once. In group I/Rc5, colchicine continued p.o. once daily for five days. Tissue malonyldialdehite (MDA), superoxide dismutase (SOD), glutathione peroxidase (GPx) and catalase (CAT) were measured for evaluating the oxidative stress. Apoptosis levels shown with Caspase-3 staining and mean seminiferous tubular diameter (MSTD), germinal epithelial cell thickness (GECT), and mean testicular biopsy score (MTBS) were used to evaluate the germ cell damage. Results: Decreased protein MDA levels therewithal increased SOD, CAT and GPx levels achieved in I/Rc5 group when compared to I/R group and did not differ from the I/Rp group (p<0.05). MSTD, GECT, and JS were better in I/Rc5 than I/Rp which showed the natural course of I/R damage in testis (p<0.005). Caspase 3 positivity, as an apoptosis indicator, were significantly lower (p<0.05) in I/Rc5 group in comparison with I/R, I/Rc1, and I/Rp groups. Conclusion: The usage of colchicine as a complementary treatment after definitive surgery reduce early-onset ischemia-reperfusion damage and diminishes apoptosis.